Efektivitas Suhu dan Lama Pasteurisasi Pada Mutu Pasta Bawang merah (Alllium Cepa Var. Aggregatum) Kemasan Standing Pouch - Lorine Tantalu; Rozana Rozana; Isrofatin Isrofatin (Politeknik Negeri Lampung., 2018)
Shallotpaste is an alternative product which can be applied as a spice, one of which is onionpaste. This study aims to determine the temperature and duration of shallot pastepasteurization before being processed into onion paste in standing pouch package.Randomized block design (RBD) 2x3 used as design experiments with pasteurizationtemperature treatment as a T factor, consisting of 2 levels, namely low-temperature longtime (LTLT), called T1, that is red onion paste heated at 65oC for 30 minutes, and high-temperature short time (HTST), called T2, that is red onion paste heated at 75oC for 15 seconds. While the S factor is the storage time consists of 5 levels, namely 4, 8 and 12 days.Storage is carried out at room temperature (27.5oC) with 3 replications. The quality observed was physical appearance, reinforced by the test parameters used including TPCand total acid. The results showed that there were changes in color and aroma that occurredafter 12 days storage into brownish yellow due to enzymatic performance. 60oC pasteurization temperature in 30 minutes is recommended for processing onion paste seenfrom the TPC value below the maximum threshold of SNI with a maximum mean value of9.103 CFU /g.